A probabilistic mix-critical task scheduling algorithm for wireless networked control system. (2017) - Lin, Qiang; Wu, Guowei; Song, Zihao; Xu, Chen
As a special application of real-time systems, a wireless networked control system (WNCS) is a control system wherein the control loops are closed through a wireless communication network. In WNCSs, tasks have different time constraints as well as critical requirements, therefore, how to schedule mix-critical tasks is extremely important. However, traditional mix-critical task scheduling algorithms for WNCSs usually suffer from long transmission delay and high failure rate, which hinders the performance of WNCSs. In this paper, we propose a probabilistic real time scheduling (PRTS) algorithm for solving scheduling problems. We introduce a schedulability analysis scheme for testifying whether a group of tasks can be scheduled or not. Then the scheduling algorithm PRTS is developed, which aims at enhancing the successful rate of scheduling and reducing the real-time transmission delay. At last, several simulations are conducted to show the advantages of our scheme. Simulation results reveal that PRTS has a higher ability in solving the mix-critical task scheduling problem. We conclude that PRTS is feasible to be used in WNCS.